Improved acidosis correction and recovery of mesothelial cell mass with neutral-pH bicarbonate dialysis solution among children undergoing automated peritoneal dialysis - Haas, Susanne; Schmitt, Claus P.; Arbeiter, Klaus; Bonzel, Klaus-Eugen; Fischbach, Michel; John, Ulrike; Pieper, Anne-Kathrin; Schaub, Thomas P.; Passlick-Deetjen, Jutta; Mehls, Otto; Schaefer, Franz (Journal of the American Society of Nephrology, 2003)
Acid-base balance and peritoneal membrane longevity are of utmost relevance for pediatric patients undergoing peritoneal dialysis (PD). PD fluids with neutral pH and reduced glucose degradation product contents are considered more biocompatible, because they preserve peritoneal cell functions in vitro. To investigate the clinical effects of a novel PD fluid buffered with 34 mM pure bicarbonate at neutral pH, a randomized, prospective, crossover comparison with conventional, acidic, 35 mM lactate PD fluid was performed for two consecutive 12-wk periods with 28 children (age, 6 mo to 15 yr) undergoing automated PD (APD).
Gesehen am 13.01.2021